Synthesis of SiO₂ matrices doped with some inorganic compounds - Blank, T.A.; Ganina, I.I.; Malyukin, Yu.V.; Eksperiandova, L.P. (Functional Materials, 2009)
The properties of silicon dioxide xerogels doped with salts and nanoparticles of inorganic compounds have been studied. Optimization of the synthesis and annealing conditions of SiO₂ matrices made it possible to increase essentially the microhardness of the doped samples. Using the aquametry technique, there was established the distribution mechanism of the of titanium oxide nanoparticles in the xerogel matrix intended to develop the new generation of luminescent materials. To obtain a moisture-resistant material, with increased service life, it has been proposed to dope the xerogel matrices with titanium oxide nanoparticles or to treat the undoped matrices with nitrocellulose lacquer. Досліджено властивості ксерогелів на основі оксиду кремнію, допованого солями та наночастинками неорганічних сполук. Оптимізація умов синтезу та відпалу SiO₂-матриць дозволила значно збільшити мікротвердість легованих зразків. Способом акваметрії встановлено механізм розподілу наночасток оксиду титану у матриці ксерогелю, яка є основою для створення люмінесцентних матеріалів нового покоління. Для отримання вологостійкого матеріалу з подовженим строком експлуатації запропоновано легувати матриці ксерогелю наночастинками діоксиду титану або обробляти нелеговані матриці цапон-лаком. Изучены свойства ксерогелей на основе оксида кремния, допированного солями и наночастицами неорганических соединений. Оптимизация условий синтеза и отжига SiO₂-матриц позволила значительно увеличить микротвердость легированных образцов. С привлечением акваметрии установлен механизм распределения наночастиц оксида титана в матрице ксерогеля, являющейся основой для создания люминесцентных материалов нового поколения. Для получения влагостойкого материала с увеличенным сроком эксплуатации предложено легировать матрицы ксерогеля наночастицами оксида титана или проводить обработку нелегированных матриц цапон-лаком.